Research on the Relationship Between Economic Policy Uncertainty and Executive Pay Gap - Liu, Lifang (Journal of Education, Humanities and Social Sciences, 2025)
In recent years, with the prosperity of China’s economy and the increasing comprehensive national power, changes in macroeconomic policies have become more frequent, and the resulting external uncertainty has had a significant impact on firms’ adjustment of their executive compensation gaps. This paper explores the relationship between economic policy uncertainty and the internal pay gap of corporate executives based on the data of 2009-2019 China’s Shanghai and Shenzhen A-share listed companies. The study shows that economic policy uncertainty significantly widens the intra-executive pay gap, and there is significant heterogeneity in the nature of corporate ownership, board size, the size of the proportion of female executives and whether they are high-tech enterprises. Further analysis shows that it significantly reduces the external pay gap for executives. The findings of this paper improve the research on the impact of macroeconomic policy changes on executive compensation gap in micro enterprises in China, and also provide a reference for further promoting compensation system reform in China.